TRANSFORMASI PERENCANAAN SDM BERBASIS NILAI ISLAM DALAM ADMINISTRASI PENDIDIKAN UNTUK MEWUJUDKAN MUTU BERKELANJUTAN - Ramadhani, Rivana Novi; Junaris, Imam (Jurnal Administrasi Pendidikan Indonesia, 2025)
The rapid changes brought about by globalization and the growing demand for sustainability have posed complex challenges for Islamic educational institutions, making the integration of Islamic values into human resource management highly relevant. Many Islamic educational institutions still manage their human resources in an administrative manner without considering spiritual and moral dimensions, creating a gap between the ideal vision of Islamic education and pragmatic managerial practices. This study aims to analyze the transformation of human resource planning based on Islamic values as a strategic starting point for school principals in realizing all functions of educational administration oriented toward sustainable Islamic educational quality. This research employs a qualitative library research approach involving content analysis of primary and secondary literature and cross-source triangulation to ensure the validity of the findings. The results indicate that the transformation of human resource planning based on Islamic values includes the integration of five core values—amanah (trustworthiness), itqan (professional excellence), ihsan (benevolence), syura (consultation), and adil (justice)—throughout all planning processes, from needs analysis, recruitment, and training to evaluation. This integration transforms human resource policies into instruments for character building and spiritual development. The approach produces educators who are not only professionally competent but also possess high integrity and strong institutional loyalty. Thus, this transformation is identified as a strategic effort to enhance the sustainable quality of Islamic education, where educational quality is measured not only by academic achievement but also by the institution’s success in developing insan kamil—individuals who are knowledgeable, virtuous, and committed to the welfare of the ummah.